Optimization of the Performance of Pati Regency Police Department Satintelkam in Prostitution Area Demolition to Maintain Public Security and Order - Mustaqim, Manggala Margi (Advances in Police Science Research Journal, 2024)
The focus of this writing is optimizing the performance of Pati Regency Police Intelligence Unit in investigating, securing and mobilizing the demolition of prostitution areas. The emphasis on this writing is considered important to be done because the prostitution area that has been exist for a long time is very disturbing the community and the Forkopimda of Pati Regency got pressed by many parties to take firm action against the existence of prostitution area. Intellegence Unit as the front guard in overseeing the demolition of the prostitution area has the obligation to optimize its performance in investigation, securing and mobilizing in order to comply with Perkabik No. 1, 2 and 3 of 2013. This writing has the objectives to describe the performance of the Intelligence Unit in cases of dismantling prostitution areas and to identify and describe problems that make the performance of the Intelligence Unit not optimal and to optimize the performance of the Intelligence Unit in overseeing cases of demolizing prostitution areas. Theory used in this writing is SWOT theory and POAC management theory as analysis tools to analyze internal problems such as the performance members of the Intelligence Unit and external problems for instance opposition groups. As for the concepts used are the optimization concept, Intellegence Unit performance concept, prostitution area concept and the concept of security and public order. The method used is qualitative with descriptive analysis to process data and field research to obtain data directly by direct observation. Primary and secondary data resources use data triangulation to obtain data validity. The result of the research conduct by author are that the performance of the Intelligence Unit has not been optimal according to Perkabik No. 1, 2 and 3 of 2013, as well as optimization that have not been implemented. The conclusion of this writing is that the performance of Intelligence Unit must comply with the Perkabik and efforts to optimze the performance of the Intelligence Unit have not been carried out because there are many limit and lack of coordination between Pati Regency stakeholders. Keywords : Performance, prostitution area, coordination Fokus penulisan ini adalah optimalisasi kinerja Satuan Intelkam Polresta Pati dalam kegiatan penyelidikan, pengamanan dan penggalangan terhadap pembongkaran kawasan prostitusi. Penekanan pada penulisan ini dianggap penting untuk dilakukan karena kawasan prostitusi yang telah lama berdiri sangat meresahkan masyarakat dan pihak Forkopimda Kabupaten Pati mendapat tekanan dari berbagai pihak untuk melakukan tindakan tegas terhadap kawasan prostitusi ini. Satuan Intelkam sebagai garda terdepan dalam mengawal pembongkaran kawasan prostitusi berupaya mengoptimalkan kinerja dalam penyelidikan, pengamanan dan penggalangan agar sesuai dengan Perkabik No.1, 2 dan 3 Tahun 2013. Penulisan ini memiliki tujuan untuk menguraikan kinerja Satuan Intelkam dalam kasus pembongkaran kawasan prostitusi dan mengidentifikasi serta mendeskripsikan permasalahan yang membuat kinerja Satuan Intelkam tidak optimal serta upaya pengoptimalan kinerja Satuan Intelkam dalam mengawal kasus pembongkaran kawasan prostitusi. Penggunaan teori dalam penulisan ini yaitu teori SWOT dan teori manajemen POAC sebagai pisau analisis terhadap permasalahan internal yaitu kinerja anggota Satuan Intelkam dan eksternal yaitu kelompok oposisi. Sedangkan untuk konsep yang dipakai adalah konsep optimalisasi, konsep kinerja Satuan Intelkam, konsep kasus, konsep pembongkaran, konsep kawasan prostitusi dan konsep keamanan dan ketertiban masyarakat. Metode yang digunakan adalah kualitatif dengan deskriptif analisis untuk mengolah data dan penelitian lapangan (field research) guna mendapatkan data secara langsung dengan pengamatan langsung. Sumber data primer dan sekunder, menggunakan triangulasi data untuk memperoleh validitas data. Hasil penelitian yang dilakukan penulis yakni kinerja Satuan Intelkam belum optimal sesuai dengan Perkabik Nomor 1, 2 dan 3 Tahun 2013, serta upaya optimalisasi yang belum bisa dilaksanakan. Simpulan penulisan ini adalah kinerja Satuan Intelkam harus menyesuaikan dengan Perkabik dan upaya optimalisasi kinerja Satuan Intelkam belum dilaksanakan karena terdapat banyak keterbatasan dan kurangnya koordinasi dengan stakeholder Kabupaten Pati. Kata Kunci : Kinerja, kawasan prostitusi, koordinasi